2015
DOI: 10.1111/jre.12309
|View full text |Cite
|
Sign up to set email alerts
|

Gene‐expression analysis of cementoblasts and osteoblasts

Abstract: Objective The purpose of this study was to assess differences in gene expression between cementoblasts and osteoblasts using gene profiling of cell populations isolated directly from osteocalcin-GFP transgenic mice. Background Cementum and bone are similar mineralized tissues, but cementum accumulates much more slowly, does not have vasculature or innervation or undergo remodeling. Despite these differences, there are no well-established markers to distinguish cementoblasts from other mature mineralizing cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 30 publications
(49 reference statements)
2
30
0
1
Order By: Relevance
“…Recently, several studies have shown the participation of Wnt6, Barx1, ptprz1, and other genes in the regulation of Wnt/β-catenin signalling and their involvement in the development of malignant tumours [31][32][33][34][35][36][37][38][39][40][41]. These ndings support our hypothesis that dlx6-as1 may affect the mRNA expression of Wnt6, Barx1, ptprz1 and other genes through ceRNA network to regulate Wnt/β-catenin signalling and participate in the distant bone metastasis of breast cancer.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Recently, several studies have shown the participation of Wnt6, Barx1, ptprz1, and other genes in the regulation of Wnt/β-catenin signalling and their involvement in the development of malignant tumours [31][32][33][34][35][36][37][38][39][40][41]. These ndings support our hypothesis that dlx6-as1 may affect the mRNA expression of Wnt6, Barx1, ptprz1 and other genes through ceRNA network to regulate Wnt/β-catenin signalling and participate in the distant bone metastasis of breast cancer.…”
Section: Discussionsupporting
confidence: 88%
“…Wnt/β-catenin signalling is critical in numerous cellular processes such as proliferation, invasion, and migration [31]. The involvement of Wnt/β-catenin signalling has been demonstrated in several malignant tumours including breast cancer and Wnt/βcatenin activation promotes tumour cell growth and metastasis [31,32]. Previous studies have shown that Wnt activation inhibits memory T cells by reducing key transcription factors produced by these cells [33].…”
Section: Discussionmentioning
confidence: 99%
“…Oc-GFP has also been used to isolate cementoblasts, as it is expressed in cementoblasts, cementocytes and odontoblasts but not PDL cells. [47]…”
Section: Identification Of Pre-osteoblasts/osteoblastsmentioning
confidence: 99%
“…Studies of mouse genetics and human disease phenotypes indicate that cementum and bone share regulatory pathways and key developmental influences (Bosshardt, ; Foster et al, ). In contrast to bone, cementum accumulates more slowly, contains no vasculature, and undergoes no remodeling (Matthews et al, ). Cementoblasts, which form cementum, are differentiated from progenitor cells in periodontal ligaments and resemble osteoblasts (J. Liao et al, ).…”
Section: Introductionmentioning
confidence: 99%